2012
DOI: 10.1073/pnas.1119741109
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of mRNA decay intermediates in Saccharomyces cerevisiae

Abstract: The general pathways of eukaryotic mRNA decay occur via deadenylation followed by 3′ to 5′ degradation or decapping, although some endonuclease sites have been identified in metazoan mRNAs. To determine the role of endonucleases in mRNA degradation in Saccharomyces cerevisiae, we mapped 5′ monophosphate ends on mRNAs in wild-type and dcp2Δ xrn1Δ yeast cells, wherein mRNA endonuclease cleavage products are stabilized. This led to three important observations. First, only few mRNAs that undergo low-level endonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 29 publications
9
66
0
Order By: Relevance
“…Sequencing of the spliced product revealed that the 59ss reported here and a more downstream 39ss at nucleotide +1672 were used ( Fig. 4A; Harigaya and Parker 2012). A BP consensus located 12 nucleotides (nt) upstream of this 39ss was proposed; however, usage of this element was not experimentally validated.…”
Section: Smd Regulates Gene Expression Genes and Development 2029mentioning
confidence: 99%
See 2 more Smart Citations
“…Sequencing of the spliced product revealed that the 59ss reported here and a more downstream 39ss at nucleotide +1672 were used ( Fig. 4A; Harigaya and Parker 2012). A BP consensus located 12 nucleotides (nt) upstream of this 39ss was proposed; however, usage of this element was not experimentally validated.…”
Section: Smd Regulates Gene Expression Genes and Development 2029mentioning
confidence: 99%
“…However, the biological relevance of this splicing event had not been addressed (Harigaya and Parker 2012). Sequencing of the spliced product revealed that the 59ss reported here and a more downstream 39ss at nucleotide +1672 were used ( Fig.…”
Section: Smd Regulates Gene Expression Genes and Development 2029mentioning
confidence: 99%
See 1 more Smart Citation
“…Specific PARE has been developed for the study of plant miRNA processing by specifically amplifying miRNA processing intermediates (Bologna et al, 2013). Although these approaches have been used to profile mRNA degradation intermediates in mutants impaired in XRNs or proteins with endonucleolytic activity (German et al, 2008;Harigaya and Parker, 2012;Schmidt et al, 2015), the interpretations of some results remain challenging because the complexity of the RNA degradome is currently still largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Cap substitution by lariat capping is presumably a stabilizing modification of mRNA because decapping followed by 5 ′ -3 ′ decay is the predominant cytoplasmic degradation pathway and because much of the 3 ′ -5 ′ degradation is dependent on translation competence and thus also indirectly involves the m 7 G cap (Harigaya and Parker 2012). In addition, the lariat cap is resistant in vitro to yeast debranching enzyme (Nielsen et al 2005) and the Xrn1p 5 ′ -3 ′ exonuclease ( Fig.…”
Section: Lc-gfp Mrnas Exhibit Long Half-livesmentioning
confidence: 99%